login
a(n) = 6*a(n-1) - 9*a(n-2) + n + 1.
1

%I #14 Jul 28 2015 15:34:00

%S 1,1,1,2,9,43,185,732,2737,9845,34449,118102,398585,1328607,4384393,

%T 14348912,46633953,150663529,484275617,1549681962,4939611241,

%U 15690529811,49686677721,156905298052,494251688849

%N a(n) = 6*a(n-1) - 9*a(n-2) + n + 1.

%H <a href="/index/Rec#order_04">Index entries for linear recurrences with constant coefficients</a>, signature (8, -22, 24, -9).

%F a(n) = (36 + (n-4)*3^n + 9*n)/36.

%F O.g.f.: -x*(-1+7*x-15*x^2+8*x^3)/((-1+x)^2*(3*x-1)^2). - _R. J. Mathar_, Dec 10 2007

%p A121365:= n-> (36 + (n-4)*3^n + 9*n)/36: seq(A121365(n), n=1..30); # _Wesley Ivan Hurt_, Apr 29 2014

%t Table[(9*(n+4)+(n-4)*3^n)/36, {n,25}]

%Y Cf. A121968.

%K nonn,easy

%O 1,4

%A _Zak Seidov_, Sep 06 2006